Entering a new era of quantifying glutamate clearance in health and disease. Issue 6 (22nd February 2021) - Brymer, Kyle J.; Barnes, Jocelyn R.; Parsons, Matthew P.
Abstract: Glutamate transporter proteins, expressed on both neurons and glia, serve as the main gatekeepers that dictate the spatial and temporal actions of extracellular glutamate. Glutamate is essential to the function of the healthy brain yet paradoxically contributes to the toxicity associated with many neurodegenerative diseases. Rapid transporter‐mediated glutamate uptake, primarily occurring at astrocytic processes, tightens the efficiency of excitatory network activity and prevents toxic glutamate build‐up in the extracellular space. Glutamate transporter dysfunction is thought to underlie myriad central nervous system (CNS) diseases including Alzheimer and Huntington disease. Over the past few decades, techniques such as biochemical uptake assays and electrophysiological recordings of transporter currents from individual astrocytes have revealed the remarkable ability of the CNS to efficiently clear extracellular glutamate. In more recent years, the rapidly evolving glutamate‐sensing "sniffers" now allow researchers to visualize real‐time glutamate transients on a millisecond time scale with single synapse spatial resolution in defined cell populations. As we transition to an increased reliance on optical‐based methods of glutamate visualization and quantification, it is of utmost importance to understand not only the advantages that glutamate biosensors bring to the table but also the associated caveats and their implications for data interpretation. In this review, we summarize the strengths and limitations of the commonly used methods to quantify glutamate uptake. We then discuss what these techniques, when viewed as a complementary whole, have told us about the brain's ability to regulate glutamate levels, in both health and in the context of neurodegenerative disease.